FORMULASI DAN UJI MUTU FISIK SABUN PADAT EKSTRAK DAUN PEPAYA (Carica papaya L.) 30% SEBAGAI ANTIJERAWAT - Dewi Riskha Nurmalasari (AKADEMI FARMASI JEMBER, 2022)
Acne is a skin disease caused by Propiniobacterium acne, and Staphylococcus aureus. To treat acne needed anti acne. In this reseacrh using medicinal plants as anti acne. These plants are efficious for anti acne. The genus Carica reported to contain papain enzym compounds. One type of plant has an anti acne activity with papain. Papain leaves (Carica papaya L) obtained from farmers Umbulrejo Umbulsari Jember. The papaya leavesis extracted with etanol 97%. Papaya leavest extract then made a solid soap, with 30% concentration of extract papaya leaves. The active inggredience is extract papaya leaves, NaOH as basa, oleum rosae as corigen odoris, and distilled water as a solvent. In this reseacrh, several physical quality tests of solid soap were carried out. The results of organoleptis test is this soap has a hard shape, the colours is light green, and the scent of soap smell rosae oil. The test results are recorded on the data collection sheet. Average of pH test showed 11, that entered in the range. The results of water content have an average of 8.2%, it shows that the soap meets the demand. The next test is the free fatty acid test results from the test that is 0.87%, the sign the results enter the range. Keywords: Papaya leaves, Solid soap, Physical quality test